2016
DOI: 10.1038/nphys3700
|View full text |Cite
|
Sign up to set email alerts
|

Measuring multipartite entanglement through dynamic susceptibilities

Abstract: Entanglement plays a central role in our understanding of quantum many body physics, and is fundamental in characterising quantum phases and quantum phase transitions. Developing protocols to detect and quantify entanglement of many-particle quantum states is thus a key challenge for present experiments. Here, we show that the quantum Fisher information, representing a witness for genuinely multipartite entanglement, becomes measurable for thermal ensembles via the dynamic susceptibility, i.e., with resources … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
345
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(371 citation statements)
references
References 73 publications
(116 reference statements)
19
345
0
1
Order By: Relevance
“…That is, the SLD characterizes the most informative measurements about λ. Importantly enough, the QFI is also a witness of multipartite entanglement among the individual constituents of a many-body system [39][40][41][42].…”
Section: Parameter Estimation In Thermal Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the SLD characterizes the most informative measurements about λ. Importantly enough, the QFI is also a witness of multipartite entanglement among the individual constituents of a many-body system [39][40][41][42].…”
Section: Parameter Estimation In Thermal Statesmentioning
confidence: 99%
“…For instance, if the parameter to be estimated is temperature, the specific heat is the relevant figure of merit and, as we will see below, what limits the sensitivity of a magnetometer is its magnetic susceptibility [26,33,36,39,[45][46][47][48].…”
Section: Parameter Estimation In Thermal Statesmentioning
confidence: 99%
“…In particular, it has been shown that the entanglement entropy shows a logarithmic divergence at the critical point of the quantum phase transition [31,32]. Similar divergence in the entanglement properties of the ground state at the critical point has also been observed in other systems, like the Dicke model or the transverse field Ising model [33,34]. Moreover, the dynamics of the von Neumann entropy of a single spin in the Lipkin-Meshkov-Glick model has also been investigated [35].…”
Section: Introductionmentioning
confidence: 78%
“…Notably, even there, β remains smaller than 2, implying that multipartite entanglement cannot be detected using local operators involving (linear combinations of) c i and c † i . This results enlarges the picture achieved for the LR Kitaev chain [47,53].…”
mentioning
confidence: 81%